Tackling hypo and hyper sensory processing heterogeneity in autism: From clinical stratification to genetic pathways. Issue 2 (4th December 2022) - Lefebvre, Aline; Tillmann, Julian; Cliquet, Freddy; Amsellem, Frederique; Maruani, Anna; Leblond, Claire; Beggiato, Anita; Germanaud, David; Amestoy, Anouck; Ly‐Le Moal, Myriam; Umbricht, Daniel; Chatham, Christopher; et al.
Abstract: As an integral part of autism spectrum symptoms, sensory processing issues including both hypo and hyper sensory sensitivities. These sensory specificities may result from an excitation/inhibition imbalance with a poorly understood of their level of convergence with genetic alterations in GABA‐ergic and glutamatergic pathways. In our study, we aimed to characterize the hypo/hyper‐sensory profile among autistic individuals. We then explored its link with the burden of deleterious mutations in a subset of individuals with available whole‐genome sequencing data. To characterize the hypo/hyper‐sensory profile, the differential Short Sensory Profile (dSSP) was defined as a normalized and centralized hypo/hypersensitivity ratio from the Short Sensory Profile (SSP). Including 1136 participants (533 autistic individuals, 210 first‐degree relatives, and 267 controls) from two independent study samples (PARIS and LEAP), we observed a statistically significant dSSP mean difference between autistic individuals and controls, driven mostly by a high dSSP variability, with an intermediated profile represented by relatives. Our genetic analysis tended to associate the dSSP and the hyposensitivity with mutations of the GABAergic pathway. The major limitation was the dSSP difficulty to discriminate subjects with a similar quantum of hypo‐ and hyper‐sensory symptoms to those with no such symptoms, resulting both in a similar ratio score of 0. However, the dSSP could be a relevant clinical score, and combined with additional sensory descriptions, genetics and endophenotypic substrates, will improve the exploration of the underlying neurobiological mechanisms of sensory processing differences in autism spectrum. Lay Summary: To explore the hypo/hyper‐sensory profile among autistic individuals and its link with genetic alterations in GABA‐ergic and glutamatergic pathways, we constructed the differential Short Sensory Profile (dSSP) from the Short Sensory Profile (SSP) of 1136 participants (533 autistic individuals, 210 relatives, and 267 controls). Groups differed in the mean dSSP, which tended to be associated with mutations of the GABAergic pathway highlighting the interest of combining dSSP with additional sensory descriptions, genetics and endophenotypic substrates to explore ASD's sensory differences.